(untitled) (Carte Romanze, 2021)
The comparative study of the old Spanish translation of the Decameron shows the adaptation of Boccaccio’s work to the new public, which determined its reception and its projection in the Hispanic literature during the following centuries. This work focuses on a series of variations identified in the 15th century translation, to study the change in the overall conception of the work and in the literary model to which they respond: if Boccaccio inaugurated the novella genre with the Decameron, the Spanish version seems to indicate a clear return to the literary characteristics of the traditional exempla.